The Babylonian disputation poems : with editions of the series of the Poplar, Palm and vine, the Series of the spider, and the Story of the poor, forlorn wren - Jiménez, Enrique, 1985- (Culture and history of the ancient Near East,, 2017)
The Babylonian Disputation Poems studies a group of ancient Babylonian poems featuring discussions between animals and trees. It contains editions of several new texts as well as an assessment of the genre and its impact on later traditions of literary disputations.